Dakwah Virtual Yayasan Spirit Dakwah Indonesia (SPIDI) Tulungagung - Mochammad Sinung Restendy (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
virtual communication can not be separated from an internet media that uses it as a means of communication, here looks a shift in style or human habits in communicating convey information with each other. Because today humans do not have to communicate at the same time and place. Challenges Globalization and technological development is what makes the national identity and local ethnicity attractive, there is inequality and meet a dead end resulting in social disintegration. Youth is now and easily infected by the virus Fast Food Culture, Fun behavior of hedons and fashion trend of western. Young people show themselves in the wrong way and way, they are not ashamed to display unethical photos on social media accounts, pornography and other issues. Based on the background of the above problems the author makes a conceptual article